Functional outcomes of rehabilitation in patients with subacute stroke on haemodialysis - Goro Shinjo; Yohei Otaka; Kaori Muraoka; Hiroki Ebata; Meigen Liu
Objective: To examine functional outcomes in patients with subacute stroke who are on haemodialysis. Design: Observational cohort study. Subjects: Patients with stroke who were admitted to rehabilitation wards between April 2011 and August 2016 were retrospectively enrolled. Methods: Data on the Functional Independence Measure (FIM) and discharge destination were collected from medical records as outcomes. Outcomes were compared for patients who received haemodialysis and those who did not. Multiple regression analyses were carried out to explore the impact of haemodialysis on functional outcomes. Results: Among 859 patients, 34 (mean age 63.6 years (standard deviation (SD) 11.7)) required haemodialysis while staying in rehabilitation wards. One hundred patients not receiving haemodialysis (mean age 70.7 years (SD 13.8) ) were randomly selected as controls. The total FIM score at discharge, FIM gain, FIM efficiency, FIM effectiveness, and discharge destination were not significantly different between the 2 groups (p > 0.05). Multiple regression analysis, adjusted for other confounding factors, found no significant difference in total FIM score between groups at discharge (p = 0.427). Conclusion: Dialysis was not an inhibitory factor affecting outcomes during subacute rehabilitation in patients with stroke. Rehabilitation should be considered for patients with subacute stroke requiring haemodialysis, in order to provide every opportunity to achieve adequate functional outcomes.